Quality Assessment of Young Sparkling Wines of Crimean Indigenous Grape Varieties - Igor P. Lutkov; Alexander S. Makarov; Natalia A. Shmigelskaya (Техника и технология пищевых производств)
Most domestic sparkling wines are made of traditional champagne grape varieties. However, indigenous Crimean cultivars could increase the output of high-quality original beverages if a proper technology was introduced. This research featured young sparkling wines from Crimean grape varieties, i.e., Soldaya, Shabash, Kokur Beliy, Sary Pandas, Kefesiya, Dzhevat Kara, and Ekim Kara. Organic acids, sugars, glycerin, phenolic substances, and ethanol were determined by high performance liquid chromatography; the content of amine nitrogen was measured by formalin titration. The optical profile of the wine samples was subjected to the colorimetric method while their foamy properties were studied by bubbling the samples in a measuring cylinder. The sparkling properties depended on the rate of CO2 desorption; the volumetric method made it possible to define the CO2 content; the viscosity was measured using a viscometer. The sensory assessment followed State Standard 32051-2013, ISO 5492:2008, and ISO 11035:1994. The samples of Kokur Beliy, Sary Pandas, and Soldaya received high tasting ratings (≥ 9.0 points), as did the red variety of Kefesiya (8.95 points). They demonstrated a clear typical aroma and a harmonious taste, as well as good foamy and sparkling properties. The maximal foam volume correlated with amine nitrogen (r = 0.762) while the sparkling properties correlated with the mass fraction of bound CO2 (r = 0.977). The red sparkling wine from the Kefesiya variety had a dark garnet color due to its high anthocyanins. It also contained quercetin and glycoside, which are known for their biological (P-vitamin) activity and powerful antioxidant properties. The early low-sugar (< 18 g/100 cm3) varieties of Dzhevat Kara and Ekim Kara had the same acidity but demonstrated a less diverse phenolic profile and were paler in color. In this research, the indigenous Crimean grape cultivars of Kokur Beliy, Sary Pandas, Soldaya, and Kefesia showed good prospects for young sparkling wines. Other varieties needed special technologies to preserve their typical properties and the aroma/taste balance. The new technology makes it possible to obtain unique high-quality products right in the harvest year, thus increasing the range and volume of sparkling wine production.